Gene expression signatures in early breast cancer: Better together with clinicopathological features. (July 2022) - Oliveira, Leandro Jonata Carvalho; Amorim, Larissa Costa; Megid, Thais Baccili Cury; de Resende, Cristiano Augusto Andrade; Mano, Max S.
Abstract: Breast cancer (BC) is a highly heterogeneous disease, characterized by a variety of subtypes with distinct biological, molecular, and clinical behavior. Standard clinicopathological and tumor biology information (as assessed by gene expression signatures–GES), have provided enhanced prognostic and predictive information in both node-negative(N0) and positive(N +), hormonal receptor positive/human epidermal growth factor 2 negative (HR+/HER2–) early breast cancer (EBC). Herein, we comprehensively review the clinical data of 5 commonly used GES, namely, Oncotype DX(ODX)®; MammaPrint (MP)®; Prosigna®; Breast Cancer Index (BCI)® and Endopredict® – with sections specifically addressing the role of GES in special histologic subtypes, premenopausal women, late recurrence and adjuvant treatment de-escalation. Highlights: Breast cancer (BC) is a heterogeneous disease in terms of molecular alterations, clinical course, response to treatment and prognosis. The integration of clinicopathological features with gene expression signatures optimizes prognostic information in HR+ /HER2- early-stage (BC). Reliable gene expression signatures are currently unavailable for premenopausal, node-positive HR+ /HER2- patients. Histologic subtypes typically associated with an excellent prognosis have a lower than 5% rate of a high Oncotype DX recurrence score. Gene expression signatures such as Prosigna®, Breast Cancer Index® and Endopredict® provide prognostic information for late recurrence.